Corporate Social Responsibility as a New Direction in Company Marketing - Dziechciarz-Duda, Marta; Przybysz, Klaudia (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Today, as product life cycles are getting shorter and shorter, companies have to change their marketing strategies not only to gain customers, but also to deserve their loyalty. Improving the company's brand, which in some cases comprises 80% of corporate value, is of the utmost importance. Another new way to strengthen a company's position on the market is the Corporate Social Responsibility (CSR) approach. Investors are not concerned only with a company's profits, but with it having an overall positive impact on society. On the other hand, new attitudes to marketing are the way to meet the needs of aware and sensible customers. For this group of clients low price is no longer the most important factor - just as significant is quality of many aspects of company operations - especially management quality and the quantifiable impact a company has on society and nature. This article attempts to answer the question of whether employing aspects of CSR yields certain advantages, such as increased company value. It also asks whether investors should take into account that the company operates according to the principles of CSR. In order to answer this question, we calculated TMAI ratios (a taxonomic measure of investment attractiveness) for indexes of listed companies included in the RESPECT Index portfolio.